2002
DOI: 10.1080/09640560120100196
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable Business Sites in the Netherlands: A Survey of Policies and Experiences

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0
3

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(38 citation statements)
references
References 6 publications
1
34
0
3
Order By: Relevance
“…The majority of these studies cited insufficient incentives to adopt environmentally sustainable practices as a trap and argued for greater economic incentives [30,32,38,42,45,55,63,66,67,69,74,75,83,84,95,102,117]. Some found that there were insufficient incentives to implement a policy or comply with regulations as a result of either a lack of official accountability or a lack of public demand for action [34,36,48,54,60,82,87,108,109].…”
Section: Implementation Trapsmentioning
confidence: 99%
See 2 more Smart Citations
“…The majority of these studies cited insufficient incentives to adopt environmentally sustainable practices as a trap and argued for greater economic incentives [30,32,38,42,45,55,63,66,67,69,74,75,83,84,95,102,117]. Some found that there were insufficient incentives to implement a policy or comply with regulations as a result of either a lack of official accountability or a lack of public demand for action [34,36,48,54,60,82,87,108,109].…”
Section: Implementation Trapsmentioning
confidence: 99%
“…The first was the inadequacy or absence of consultation with the affected community [30,41,45,49,56,60,78,79,[81][82][83][84]94,95,98,99,103,110,115,120,122]. The second was a failure to adequately involve the community in the policy process [32,36,57,59,65,73,77,98,104,123].…”
Section: Implementation Trapsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some such benefits may relate to environmental issues, such as park-level regulatory compliance, or onsite recycling, but there is nevertheless an awareness of the potential economic benefits (LOWE, 1997;MARTIN et al, 1998). Indeed, in a study of Dutch ecoindustrial parks, PELLENBARG (2002) found that external economies relating to non-environmental activities (e.g., parking facilities or safety systems) were more common than environment-related ones (e.g., utility sharing or heat cascading).…”
Section: Eco-industrial Parks As a Cluster Developmentmentioning
confidence: 99%
“…Bak [1] explored the use of space by industrial companies; Ike et al [13] studied financial problems of Dutch municipalities which coincided with the surplus of industrial areas during the 1980s; van Steen [29,30] examined industrial areas as investment object from an entrepreneur's perspective; Meester [17] and Pen [23] paid attention to the relation between company migration and industrial area planning and Pellenbarg [22] examined the policy of the Dutch government to develop sustainable industrial areas. Interestingly, recent research aims increasingly on process characteristics of the redevelopment of industrial areas.…”
Section: Introductionmentioning
confidence: 99%